2020
DOI: 10.1186/s12879-020-4759-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Toxocara and Toxascaris infection among human and animals in Iran with meta-analysis approach

Abstract: Background: Toxocariasis is a worldwide zoonotic parasitic disease caused by species of Toxocara and Toxascaris, common in dogs and cats. Herein, a meta-analysis was contrived to assess the prevalence of Toxocara/Toxascaris in carnivore and human hosts in different regions of Iran from April 1969 to June 2019. Methods: The available online articles of English (PubMed, Science Direct, Scopus, and Ovid) and Persian (SID, Iran Medex, Magiran, and Iran Doc) databases and also the articles that presented in held pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 59 publications
1
38
1
Order By: Relevance
“…The disease is distributed worldwide, but particularly highly in tropical lower-resource countries. It causes significant morbidity and poses an important, yet largely unaddressed public health problem in areas of high prevalence [ 40 ]. The majority of Toxocara infections remain asymptomatic, whilst a minority develop fatal diseases of visceral larva migrans , ocular larva migrans , and covert toxocariasis.…”
Section: Discussionmentioning
confidence: 99%
“…The disease is distributed worldwide, but particularly highly in tropical lower-resource countries. It causes significant morbidity and poses an important, yet largely unaddressed public health problem in areas of high prevalence [ 40 ]. The majority of Toxocara infections remain asymptomatic, whilst a minority develop fatal diseases of visceral larva migrans , ocular larva migrans , and covert toxocariasis.…”
Section: Discussionmentioning
confidence: 99%
“…Toxocariasis is an infection that has a worldwide distribution and is a very important zoonosis due to its frequent occurrence in humans [119]. The estimate of the overall worldwide prevalence of T. canis in dogs of 11.1% represents 100 million dogs, which should alert Public Health experts and policy makers to the need for effective intervention programs [114,120]. This parasite species has high biotic potential since its eggs contaminate water, soil, grass, and pet fur [51].…”
Section: Toxocariasismentioning
confidence: 99%
“…Seroprevalence studies show a relatively high prevalence of human toxocariasis in different parts of the world [ 4 – 6 ]. In a recent study in Iran, the rate of Toxocara infection in cats and dogs, the main hosts of Toxocara , was reported to be 32.6% and 24.2%, respectively [ 7 ]. Moreover, the results of a meta-analysis study in Iran reported the rates of 0.84 to 29% for the seroprevalence of human toxocariasis in different areas of the country [ 8 ].…”
Section: Introductionmentioning
confidence: 99%